Colorimetric amine detection by vanillin-hydrazone derivatives during chicken meat spoilage - Purwono, Bambang; Nurohmah, Beta Achromi; Suharman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Two vanillin-hydrazone compounds as the colorimetric amine detection during chicken meat spoilage are described. Two hydrazone compounds (1 and 2) have been synthesized from the condensation reaction of vanillin with phenylhydrazine and 2,4-dinitrophenylhydrazine. Their properties for colorimetric recognition of amine were determined by the naked eye and UV-vis spectra. Their properties as amine indicators were investigated toward primary amine: butylamine (BA); secondary amine: dimethylamine (DMA), diethylamine (DEA); tertiary amine: triethylamine (TEA), and also ammonia (Amm). The hydrazone 1 in DMSO showed no significant color changes (colorless) after the addition of amines solution. Hydrazone 2 (5×10-5 M in DMSO) showed color changes from yellow to violet in the presence of ammonia, DEA and BA, to reddish-violet for DMA, and light brown after addition of TEA solutions. The colorimetric amine detection by vanillin-hydrazone 2 could recognize the real amine during chicken meat spoilage from yellow to light brown after 24 h storage at room temperature.